APPLICATION OF HOBBS’S ALGORITHM TO UZBEK TEXTS (TAMADDUN NURI JURNALI, 2024)
This article discusses the problem of solving coreference related to pronouns, the advantages and disadvantages of using the Hobbs algorithm to solve it. It also describes the specific features of the Hobbs algorithm and instructions for its use. The algorithm is applied to Uzbek texts and its working principle is studied.